Exploring Preservice Teachers’ Perceptions of Preparedness to Teach Students with Disabilities - Reeves, Linda M.; Giles, Rebecca M.; Johnson, Todd (Journal of the American Academy of Special Education Professionals, 2019)
The purpose of this study was to investigate the influence of initial special education experiences on elementary preservice teachers’ knowledge and comfort level regarding students with disabilities. A total of 109 preservice teachers enrolled in a dual teacher certification program (general and special education) were surveyed before and after their semester long training in special education to investigate their perceptions of preparedness to teach students with disabilities. There was a significant increase in the preservice teachers’ knowledge across all disability categories. A significant increase in their comfort level occurred across all disability categories with the exception of behavior disorders. As follow up, approximately one-third of the participants completed a questionnaire which provided additional qualitative data. The results support that field experiences with students who have disabilities seems to be an influential factor in preparing teachers to become more knowledgeable and comfortable meeting the needs of these students. The implications of this study for practice and future research are discussed.